Study on the Backlash and Stiffness Measurement System for RV Reducer - Zhao Haiming; Li Haowu; Zhu Jiayun; Nie Shuai; Cai Jinxiong (Jixie chuandong)
The backlash and stiffness are important parameters of vector rotate（ RV） reducer,a backlash and stiffness measurement system is designed. The measuring method of the fixed output,loaded input and angle tested input is put forward. The relation between input and output torque and angle of the RV reducer is used to process the data. The RV-40 E-121 reducer is tested and the model of RV reducer stiffness curve fitting is proposed,the stiffness curve of RV-40 E reducer is obtained. The backlash and stiffness of the RV-40 E reducer meet the performance requirements,which indicated that the measurement system is reasonable.